Hedging Against Exchange Rate Fluctuation Risks Using Obverse Murabaha in Islamic Banks: A Fiqhi Study - Al Momani , Israa Mousa; Al Mousa, Ali Muhammad (Dirasat: Shari'a and Law Sciences, 2021)
This paper studies the Obverse Murabahas as an Islamic hedging tool against the foreign exchange rates fluctuations, by providing a comprehensive understanding of the issue, and validating the legitimacy of this tool as an Islamic alternative. The research followed the descriptive approach by tracking the instruments of hedging against the risks of exchange rate volatility based on opposite Murabaha, whether applied in Islamic banks or put forward in the relevant references, and the analytical approach by treating the hedging instruments with opposite Murabaha and detailing them, clarifying them with applied examples, and stating their Shari'a provisions. The research concluded that hedging through this tool can be conducted by two main methods: either by cross Murabahas on different goods to the same due date, or on the same goods to the same due date. Both methods have different implementations, and therefore, have different legitimacies from an Islamic perspective. However, their major flaw is that they use multiple Murabaha transactions as nominal mediator without real commodity transactions. The study recommended the importance of holding more seminars and conferences to discuss innovative formulas for Islamic hedging.